Discovering the Stream in the Desert: Toward Homosexual Inclusion in the American Conservative Jewish Movement - Elazar Ben-Lulu (Social Sciences)
In recent decades, various communities and organizations have been working to promote LGBTQ+ inclusion and justify their equal rights. This task becomes more complex within religious communities that are based on traditional values that reject homosexuality. This historical-anthropological study presents “K’Afikim BaNegev”—a special manual that includes more than 347 pages and incorporates 73 diverse sources distributed in early 1994 in American Conservative Jewish congregations aimed at combating homophobia. I clarify how the documents reveal progressive qualitative methodologies for identifying and understanding barriers and mechanisms of community change. Textual analysis of personal letters, educational programs, workshops, and rabbinical sermons revealed two methods for creating this egalitarian change and constructing the Jewish community as a safe space for gay men and lesbian women and their family members: (1) using and promoting personal narrative (storytelling) as a channel to voice LGBTQ+ people’s stories and (2) adapting a text-centered approach that considers biblical sources as authoritative in recognizing LGBTQ+ identity. Thus, the acceptance of homosexuality was not conceptualized in terms of liberal human rights rhetoric but rather as a religious commandment. Thus, I define this novel initiative as an act of ‘queer Jewish activism,’ offering a new typology for community development and practice that advocates for LGBTQ+ individuals within contemporary religious communities.